Feasibility Test of a Monograph as a Reference for an Ethnobiology Course (Case Study on the Production of the Traditional Food Ie Bu Peudah) - Marisa Assyifa; Mulyadi; Nurdin Amin; Zuraidah; Nafisah Hanim (Educator Development Journal, 2026)
The Ethnobiology course requires a broad understanding from ethnobotany to local wisdom; however, the lack of references on Acehnese local wisdom causes students to miss out on contextual learning sources that connect local culture with biodiversity. The Ie Bu Peudah tradition holds ethnobotanical wealth consisting of 44 types of plants that have not been documented in verified learning sources. This research aims to develop a monographic book on the utilization of plants in Ie Bu Peudah as a reference for the Ethnobiology course and to assess its feasibility. The research uses a 3D R&D model (Define, Design, Develop), including needs analysis and data collection on ethnobotany through observation and interviews with the community involved in the Ie Bu Peudah tradition in Lhoknga District, Aceh Besar, drafting the book, and validation by subject matter and media experts. The resulting monographic book contains the history, 44 types of plants, the process of making, as well as the ecological and socio-spiritual values of Ie Bu Peudah. Expert validation results recommend improvements in the clarity of learning outcomes, completeness of data and image descriptions, writing of foreign/Latin terms, correction of typos, revision of the cover design, and addition of a plant classification table. The validation scores from subject matter experts were 86% and from media experts 83% (an average of 84%, very feasible). It is concluded that the Ie Bu Peudah monographic book is highly suitable as a teaching material for Ethnobiology and relevant in connecting Acehnese local wisdom with the learning outcomes of ethnobotany, ethnoecology, and the utilization of biodiversity